Challenges to Development Study in A Spatially Changing World Order (Indonesian Case Study) - Bangun Mulyo Sukojo (IPTEK Journal of Proceedings Series, 2020)
International power relations changing and how can global peace and stability be maintained? With some main theories of international relations, shows how the global order is gradually changing and discusses how selected international and regional organizations contribute to the maintenance of global peace and security. Most importantly, It was seeing the confluence of high levels of indebtedness and extremely low interest rates which limits central banks’ powers to stimulate the economy, large wealth gaps and political divisions within countries which leads to increased social and political conflicts. The COVID-19 pandemic has caused a historic setback to decades of development progress, and also exposed gaps in regional cooperation. The vertical across shows the number of COVID-19 death per million, as of August 30. The horizontal axis shows the percentage decline of GDP relative to the same quarter in 2019. It is ajusted for inflation This is a moment for reflection for policy makers across Asia and the Pacific and, as COVID-19 reshapes the world, we need to think innovatively on how future regional cooperation could be strengthened and be more agile in addressing the development challenges of our time. Disasters are usually difficult to avoid, but they can actually be mitigated. For a long time, the campaign on disaster awareness has been echoed. The idea of a disaster-aware community needs to be fully animated. The place (spatial) needs to be designed in such a way so that people are aware of the threat of disasters that can come at any time. Here we see an imbalance, on the one hand, humans are now very advanced (advanced) designing and executing many things: how to create connectivity, ease of moving, and speed of communication. However, on the other hand we fail to think about the (Geospatial) places in which humans live their lives.